1990
DOI: 10.1111/j.1399-6576.1990.tb03126.x
|View full text |Cite
|
Sign up to set email alerts
|

Side effects and complications related to interpleural analgesia: an update

Abstract: Interpleural analgesia has been successfully used for pain relief after cholecystectomy, renal surgery, breast surgery and thoracotomy. Little has been reported about side effects and complications. This article summarizes available information about adverse events collected from the literature. The survey comprises a total of 703 cases. Pneumothorax was the most frequently registered complication followed by signs of systemic toxicity and pleural effusion. Horner's syndrome, pleural infections and catheter ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…epidural, intrapleural or intercostal blocks [l l-13, [24][25][26]. Although paravertebral block can be used for a wide variety of procedures there are some contraindications to its use in thoracic surgery.…”
mentioning
confidence: 99%
“…epidural, intrapleural or intercostal blocks [l l-13, [24][25][26]. Although paravertebral block can be used for a wide variety of procedures there are some contraindications to its use in thoracic surgery.…”
mentioning
confidence: 99%
“…The technique appears very similar to that described by Alexander et al [I], who found that bupivacaine infiltration of the mesosalpinx significantly reduced the pain after Yoon (Falope) ring sterilisation. Our own study that year [2] showed that ring sterilisation was followed by significantly more pain than Hulka clip sterilisation during the first 6 h after operation. The pain associated with the Falope ring presumably arises from infarction of the tubal section drawn into the ring and/or the pull on the mesosalpinx drawn with it.…”
Section: Rectus Sheath and Mesosalpinx Block For Laparoscopic Sterilimentioning
confidence: 87%
“…A review article described that the most frequent complication of IPA was pneumothorax (2.0%), followed by systemic toxicity of local anesthetics (1.3%) and pleural effusion (0.42%). 14) Pneumothorax may occur because of air entrainment or as a result of damage to the lung parenchyma caused by the percutaneous technique of catheter placement. 15) Placement under direct vision such as our technique clearly reduces the incidence of pneumothorax.…”
Section: Discussionmentioning
confidence: 99%